The Influence of Leadership and Work Environment on Work Motivation and Its Impact on Teacher Performance at State Senior High School 14 Palembang - Anna Prima Sari; Msy. Mikial; Tri Suyantiningsih (International Journal of Management and Business Economics, 2024)
This study aims to determine and analyze the Influence of Leadership and Work Environment on Work Motivation and its Implications on Teacher Performance both directly and indirectly. The research method was conducted quantitatively using descriptive-correlation research to assess the relationship between the variables studied. The study was conducted using a validity sample of 49 people taken from the total population. The results of this study indicate that Leadership (X1) has a positive and significant effect on Work Motivation (Y1); Work Environment (X2) has a positive and significant effect on Work Motivation (Y1); Leadership (X1) has a positive and significant effect on Teacher Performance (Y2); Work Environment (X2) has a positive and significant effect on Employee Performance (Y2); Work Motivation (Y) has a positive and significant effect on Teacher Performance (Y2)